Poly[[bis(μ4-acetato-κ4O:O:O′:O′)tetrakis(μ3-acetato-κ3O:O:O′)bis(μ2-acetato-κ2O:O′)bis(μ3-hydroxido)pentanickel(II)] 2.60-hydrate] - Maximilian Pfeiffer; Berthold Stöger; Matthias Weil (IUCrData)
The title compound, {[Ni5(C2H3O2)8(OH)2]·2.60H2O}n or [Ni5(OAc)8(OH)2]·2.60H2O (OAc is the acetate anion, C2H3O2), represents a hydrated basic acetate. Its asymmetric unit comprises half of the formula unit, with one of the three unique NiII cations situated at an inversion centre. The NiII atoms are in octahedral coordination environments by O atoms of the acetato ligands and by the basic OH group. The different kinds of bridging modes (μ2, 2×μ3, and μ4 for the acetato ligands; μ3 for the OH group) lead to the formation of a framework structure with hydrophobic channels extending parallel to the main crystallographic axes. Disordered water molecules are situated in pockets close to the OH groups and are held in place by hydrogen-bonding interactions.